A CLINICAL STUDY ON SAMVARDHAN GHRITA AND SARASWAT CHURNA IN CHILDREN SUFFERING FROM BALBUDDHIMANDYA W.S.R. TO MENTAL RETARDATION - Laxmanrao Patil, *Prashant; Raut, Deokumar W. (International Journal of Ayurveda and Pharma Research, 2015)
In Ayurvedic classics, Balbuddhimandya have been used by Acharyas in the sense of mentally retarded. Many times the word Jada, Abuddha, Nirbuddhi used to mention the low intelligence. In modern world mentally retarded child consisting of below average intellectual functioning and impairment in adaptive skill. The impairments are influenced by genetic, environmental and psychosocial factor, here there are classification of mentally retarded child is also well explained in the form of educable, trainable and idiot.Ayurvedic classics have been systematic etiological background of the problem causes hypofunction of Dhee, Dhriti and Smriti. The experiment is human based clinical trials in which Samvardhan ghrita in Kashyap samhita is clearly mention that this Ghrita is useful in the treatment of Panguta, Mukata and Jadata, where as Acharya Bhavaprakasha explained Saraswat churna is very much potent act as a Medhya, increases intellect against referred disease.The Ghrita is well prepared according to procedure mention in Bhaishajya kalpana to be given orally, nasally as well as anally with Anupan taken as Koshna jal also Churna is to be given orally only.Ayurveda the parental origin of all the pathies may have its proper solution both the corners preventive as well as curative. This science is having holistic approach were Garbhadhan is treated as a holy Samskar. Simultaneously Punsavan, Simantonnayan and Jatkarm samskaras are very pious in reference to healthy newborn.As in Vedas also a special attention is given to increase the Buddhi. Medhya rasayanas and Medhya yogas explained in Ayurvedic classics improves the intelligence and memory also it is increasing the efficacy of Manovaha srotas. In the given study we found that Samwardhan ghrita and Saraswat churna together provided better results in mental retardation.